Using mixed methods to investigate school improvement and the role of leadership: an example of a longitudinal study in England - Sammons, Pamela; Davis, Susila; Day, Christopher; Gu, Qing (Emerald, 2014)
Purpose-The purpose of this paper is to discuss the use of mixed methods research in a major three year project and focuses on the contribution of quantitative and qualitative approaches to study school improvement. It discusses the procedures and multiple data sources used in studying improvement using the example of a recent study of the role of leadership in promoting improvement in primary and secondary schools’ academic results in England. Although the definition of improvement used was based on robust analyses of data on students’ academic outcomes, the mixed methods design enabled a broader perspective to be achieved.